Intra-articular hylastan versus steroid for knee osteoarthritis. - Housman, L; Arden, N; Schnitzer, T; Birbara, C; Conrozier, T; Skrepnik, N; Wei, N; Bockow, B; Waddell, D; Tahir, H; Hammond, A; Goupille, P; et al. (Springer Verlag, 2014)
PURPOSE: To assess the efficacy and safety of one and two intra-articular (IA) injections of the new viscosupplement, hylastan, compared with a single IA corticosteroid injection for pain due to knee osteoarthritis (OA). Hylastan is a high-molecular-weight hyaluronan derivative prepared from bacterial fermented sodium hyaluronate that was developed to remain in the joint for longer than most other viscosupplements. METHODS: This 6-month, double-blind, randomized, parallel group, multicenter trial enrolled patients aged ≥40 years who met American College of Rheumatology criteria for knee OA and had continued pain despite conservative treatment. Patients were randomized 1:1:1 to one of three arms: 2 × 4 mL hylastan (n = 129; arthrocentesis then IA hylastan Day 0, same treatment Week 2); 1 × 4 mL hylastan (n = 130; arthrocentesis then IA hylastan Day 0, arthrocentesis only Week 2); steroid (n = 132; arthrocentesis then IA methylprednisolone acetate 40 mg Day 0, arthrocentesis only Week 2). Participants and evaluators were blinded to treatment. The primary clinical outcome measure was change from baseline in WOMAC A pain score over all postbaseline visits to Week 26. RESULTS: Statistically significant pain reduction was observed in all three arms, with similar mean (95 % CI) changes in WOMAC A: 2 × 4 mL hylastan -0.9 (-1.0, -0.7); 1 × 4 mL hylastan -0.8 (-0.9, -0.7); steroid -0.9 (-1.0, -0.8); all P < 0.0001 versus baseline. Changes in secondary outcomes (OMERACT-OARSI and WOMAC A responder rates, patient/clinical observer global assessments, and WOMAC A1 walking pain) were similar in all three arms. Target knee adverse events were comparable for all treatments. CONCLUSIONS: Both IA hylastan injection regimens were effective in relieving pain with an acceptable safety profile. IA hylastan did not show a difference versus IA corticosteroid; therefore, the hypothesis of superior pain relief was not met. Further research is needed to compare the efficacy and safety of hylastan with other viscosupplements.